DISCREPANCY INR VALUE (INTERNATIONAL NORMALIZED RATIO) IN OPTICAL AND ELECTROMECHANICAL METHOD - Yunensie, Putri Adelia; Notopuro, Paulus B. (Journal of Vocational Health Studies, 2021)
Background: INR examination services at laboratories in hospitals and clinics use different methods and tools therefore, results of the INR examination are different. Purpose: To determine whether there are differences in the INR value between using the photo optic method and electromechanical method. Method: This study used a citrate blood sample with a ratio of blood and anticoagulant 9: 1 and used the Sysmex CA-600 device for the photo optic method and used the Thrombostat device for the electromechanical method. The sample consisted of 32 samples, namely 10 treatment samples to be analyzed and 22 normal samples. Using SPSS 25.0 to test data that was tested for normality test and in a different test. Result: The result of INR with the electromechanical method was significantly longer than INR with the photo optic method. In the hemolytic sample, the result was significantly higher than the INR result with normal samples. Conclusion: There are significant differences between results of the INR value using photo optic and electromechanical due to the difference in the detection principle between the two methods.